2006
DOI: 10.1590/s0103-50532006000600014
|View full text |Cite
|
Sign up to set email alerts
|

Raman and infrared spectroscopy studies of carbon nitride films prepared on Si (100) substrates by ion beam assisted deposition

Abstract: Filmes de nitreto de carbono, preparados por deposição assistida por feixe de íons, foram estudados pela espectroscopia de Raman e infravermelho, em função de energia de íons (200, 400, e 600 eV) e razão de chegada de íon a átomo R(I/A) de 0,9 a 2,5. A razão de composição N/C no filme, determinada por análise de detecção de recuo elástico, foi encontrada proporcional a R(I/A); porém, a formação de filme é possível somente se R(I/A) for menor do que um valor crítico da eficiência de "sputtering" químico. Esse v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The peak centered at 2013 cm −1 corresponds to the stretching vibration of the triple bonding between carbon and nitrogen (CN). Hu et al 26, Escobar−Alarco et al 27, and Sucasaire et al 28 found similar results by their infrared spectroscopy analyses of amorphous carbon nitride. Peaks of amorphous BN phases are not observed in this FTIR study.…”
Section: Resultsmentioning
confidence: 61%
“…The peak centered at 2013 cm −1 corresponds to the stretching vibration of the triple bonding between carbon and nitrogen (CN). Hu et al 26, Escobar−Alarco et al 27, and Sucasaire et al 28 found similar results by their infrared spectroscopy analyses of amorphous carbon nitride. Peaks of amorphous BN phases are not observed in this FTIR study.…”
Section: Resultsmentioning
confidence: 61%
“…2. The broad peaks at 3100-3300 cm -1 can be assigned to the stretching modes of N-H bonds in NH and NH 2 configurations and to hydroxyl group -OH which may incorporate after exposing to air [27]. The strong bands at 1200-1650 cm -1 are attributed to the stretching vibration modes of C-N heterocycles [12,28].…”
Section: Resultsmentioning
confidence: 98%
“…As shown in the figure, in the prepared samples, two peaks appear broadly centered at 1370 and 1595 cm À1 , representing the D and G bands. 32,33 Here, the D-band is associated with defective and disordered carbon, while the G-band is associated with the ideal graphite lattice of carbon. The degree of graphitization of the samples can be expressed as the relative intensity ratio (I D / I G ) of these two peaks.…”
Section: Resultsmentioning
confidence: 99%